2016
DOI: 10.5713/ajas.16.0457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein sources on production performance, egg quality, and plasma parameters of laying hens

Abstract: ObjectiveThis study was conducted to evaluate the effects of dietary protein sources (soybean meal, SBM; low-gossypol cottonseed meal, LCSM; double-zero rapeseed meal, DRM) on laying performance, egg quality, and plasma parameters of laying hens.MethodsA total of 432 32-wk-old laying hens were randomly divided into 6 treatments with 6 replicates of 12 birds each. The birds were fed diets containing SBM, LCSM100, or DRM100 individually or in combination with an equal amount of crude protein (CP) (LCSM50, DRM50,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…However, SGPT has poor specificity for liver disease in birds due to its existence in many tissues. Our results of SGOT activity (157.5 to 159 U/L) in GF were low compared to results in chickens of Wang et al ( 2017 ) (174 to 190 U/L). SGPT activity (3.1 to 3.5 U/L) in GF was in the range of results of these authors (1.83 to 3.17).…”
Section: Discussioncontrasting
confidence: 96%
“…However, SGPT has poor specificity for liver disease in birds due to its existence in many tissues. Our results of SGOT activity (157.5 to 159 U/L) in GF were low compared to results in chickens of Wang et al ( 2017 ) (174 to 190 U/L). SGPT activity (3.1 to 3.5 U/L) in GF was in the range of results of these authors (1.83 to 3.17).…”
Section: Discussioncontrasting
confidence: 96%
“…It is well established that the protein content of the egg is highly influenced by the diet of the hen ( Wang et al., 2017 ). Although most likely the chickens that laid the eggs for this study had access to very different feeds, no differences were found in the protein content of the albumen between eggs laid by the different breeds of chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Disparate results on albumen quality were presented by Gheisari and Ghayor [ 42 ], in which eggs obtained from quail fed a mixture containing 15% canola meal were characterized by a significantly better quality of this morphological element, while the best albumen quality characterized eggs from birds fed with 20% canola meal addition. A slightly different observation was made by Wang et al [ 2 ], who analyzed the quality of eggs from hens fed various alternative protein sources (including rapeseed meals). It was found that eggs from birds fed with rapeseed meals were characterized by lower quality compared to those fed with a standard feed mixture (based on soybean meal).…”
Section: Discussionmentioning
confidence: 96%
“…Protein is one of the most important balanced components of poultry feed and the source of essential amino acids. Its quality is crucial for the proper growth and good health of birds, their production and the quality of obtained eggs [ 1 , 2 ]. Currently, soybean meal is a major protein source in poultry nutrition.…”
Section: Introductionmentioning
confidence: 99%